2022
DOI: 10.11648/j.cmr.20221103.16
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Dalbavancin Monotherapy as Salvage Treatment for Bone and Joint Infection

Abstract: Bone and joint infection (BJI) treatment is challenging with significant morbidity and mortality. Dalbavancin is a semi-synthetic lipoglycopeptide analogue of the teicoplanin class that exhibits bactericidal activity and a long half-life. The use of dalbavancin may be an option in cases of gram-positive BJI. From November 2017 to April 2019, dalbavancin was used in monotherapy as a salvage option for BJI, as follows: 1500 mg, 1st (D1) and 8th (D8) days, repeated if needed. The follow-up period was of 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…While these trials provide valuable information regarding tolerability, efficacy data cannot be extrapolated for infections other than ABSSSIs. However, realworld studies showed that dalbavancin has been used for the treatment of other bacterial infections, such as bone and joint infections, prosthetic joint infections, osteomyelitis, and endocarditis [13][14][15][16][17][18]. Linezolid, also originally approved for ABSSSIs, is a striking example of an Accepted manuscript 5 antibiotic with extensive off-label use [19], which subsequently required additional research efforts to characterize its efficacy and tolerability in other indications [20].…”
Section: Introductionmentioning
confidence: 99%
“…While these trials provide valuable information regarding tolerability, efficacy data cannot be extrapolated for infections other than ABSSSIs. However, realworld studies showed that dalbavancin has been used for the treatment of other bacterial infections, such as bone and joint infections, prosthetic joint infections, osteomyelitis, and endocarditis [13][14][15][16][17][18]. Linezolid, also originally approved for ABSSSIs, is a striking example of an Accepted manuscript 5 antibiotic with extensive off-label use [19], which subsequently required additional research efforts to characterize its efficacy and tolerability in other indications [20].…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer (esophageal carcinoma) is the tenth most common cancer worldwide and the sixth leading cause of cancer-related deaths [1]. However, most esophageal cancers are detected at an advanced stage, when treatment options are limited and prognosis is poor, and conventional synchronized chemoradiotherapy or induction chemotherapy in combination with it does not improve the response rate or survival of patients [2].…”
Section: Introductionmentioning
confidence: 99%